Low-load IrO2 electrolyzed water membrane electrode as well as preparation method and application thereof
Patent Information
- Application Number
- CN202310800846.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-07-03
AI Technical Summary
The catalyst utilization rate in the existing proton exchange membrane water electrolysis is low, resulting in a high catalyst load on the membrane electrode and poor material transfer efficiency, making it difficult to reduce the amount of precious metal catalysts while maintaining high performance.
The electrospinning technology is used to disperse iridium dioxide and polymer to form a uniform spinning precursor liquid. The IrO2 nanofiber layer is obtained by electrospinning, and the anode catalytic layer is heat-pressed and transferred onto the Nafion film to form an anode catalytic layer, and then sprayed with cathode catalytic The low-load IrO2 electrolytic water film electrode was constructed.
The loading of precious metal catalysts is reduced, the utilization rate of the catalyst is improved, the three-phase reaction interface of the membrane electrode is increased, the proton conduction efficiency is improved, and a high-active, low-load IrO2 electrolytic water membrane electrode is formed.
Smart Images

Figure CN119243202A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of water electrolysis membrane electrodes, and in particular relates to a low-load IrO2 water electrolysis membrane electrode, a preparation method and application thereof. Background Art
[0002] Proton exchange membrane water electrolysis (PEMWE) has attracted the attention of many researchers due to its advantages such as high energy density and high purity of hydrogen production. Among them, iridium-based materials play a vital role in the field of proton exchange membrane water electrolysis (PEMWE) as efficient oxygen evolution reaction (OER) electrocatalysts. Since Ir reserves on the earth are relatively scarce and expensive, if we want to promote the research and application of PEMWE on a large scale, we must reduce the amount of Ir so that it can still maintain high performance at low loading.
[0003] The membrane electrode assembly (MEA), also known as the membrane electrode, is a key core component in PEMWE and an important place for material transfer and electrochemical reactions. The membrane electrode consists of three parts: proton exchange membrane, catalyst layer and gas diffusion layer. The traditional method is to directly spray the catalyst (CCM) on the proton exchange membrane. The catalyst layer on the prepared membrane electrode has a high loading (2-4 mg cm -2 ), and because the particles in the catalytic layer are densely packed, the material transfer efficiency is poor and needs to be further optimized. Increasing the three-phase reaction interface of the membrane electrode and thus improving the catalyst utilization rate is one of the effective ways to reduce the amount of precious metal catalysts used.
[0004] Therefore, the controllable construction of the membrane electrode to maximize the three-phase reaction interface, expand the proton exchange membrane / catalytic layer interface and the overall design of the rapid mass transfer channel are current research hotspots and difficulties. Summary of the invention
[0005] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a low-loading IrO2 water electrolysis membrane electrode, a preparation method and its application, so as to solve the problem of low catalyst utilization in the prior art, resulting in a high catalyst loading on the membrane electrode, and poor material transmission efficiency at the three-phase reaction interface of the membrane electrode.
[0006] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a low-load IrO2 water electrolysis membrane electrode, the preparation method comprising the following steps:
[0007] S1, dispersing iridium dioxide and a polymer in a mixed solution to obtain a uniform spinning precursor solution; wherein the mixed solution comprises a Nafion solution, water and isopropanol;
[0008] S2, electrospinning the spinning precursor solution to obtain an IrO2 nanofiber layer on a receiving device;
[0009] S3, hot-pressing and transferring the IrO2 nanofiber layer onto a Nafion membrane to form an anode catalyst layer on the Nafion membrane;
[0010] S4. Spray the cathode catalyst slurry onto the side of the Nafion membrane away from the anode catalyst layer, and form a cathode catalyst layer on the other side of the Nafion membrane through hot pressing, thereby finally preparing a low-load IrO2 water electrolysis membrane electrode.
[0011] Preferably, the polymer in step S1 includes one of polyethylene oxide, polyvinyl alcohol, polyacrylonitrile and polyvinyl pyrrolidone, and the viscosity average molecular weight of the polymer is 100,000 to 1,000,000.
[0012] Preferably, the mass ratio of iridium dioxide, polymer and Nafion solution in step S1 is (20-100): (2-20): (50-500), and the mass concentration of the polymer in the obtained spinning precursor solution is 2wt%-10wt%.
[0013] Preferably, in step S1, the total mass of the water and the isopropanol is 0 to 30 times the mass of the iridium dioxide, and the mass ratio between the water and the isopropanol is 1:1.
[0014] Preferably, the Nafion solution in step S1 is a Nafion solution with a mass percentage of 5wt% or 20wt%.
[0015] Preferably, the process parameters of the electrospinning in step S2 are: positive voltage of 4 to 20 kV, negative voltage of 0 to -3 kV, ambient temperature of 15 to 25 ° C, relative humidity of 35% to 45%, solution advancement speed of 0.01 to 0.3 ml / h, and the distance between the syringe needle and the receiving device is 10 to 20 cm.
[0016] Preferably, the receiving device in step S2 is a flat plate, grid or roller-shaped receiving device, and aluminum foil or silicone oil paper is adhered to the receiving device.
[0017] Preferably, the Nafion membrane in step S3 needs to be pretreated before transfer, specifically, the Nafion membrane is cut into the required size, placed in a 3wt% to 10wt% hydrogen peroxide solution and heated for 1 hour, then washed with ultrapure water, and then placed in a 0.5mol / L sulfuric acid solution and heated for 1 hour. After washing with ultrapure water, a pure Nafion membrane is obtained.
[0018] Preferably, the temperature of the hot-pressing transfer in step S3 is 130-140° C., the pressure of the hot-pressing transfer is 1-3 MPa, and the time of the hot-pressing transfer is 2-5 min.
[0019] Preferably, in step S4, according to the components of the cathode catalyst slurry, the cathode catalyst slurry includes 1 part of Pt / C catalyst, 1 to 10 parts of 5 wt% Nafion solution, 5 to 15 parts of water and 5 to 15 parts of isopropanol.
[0020] Preferably, the temperature of the hot pressing in step S4 is 130-140° C., the pressure of the hot pressing is 4-6 MPa, and the time of the hot pressing is 1-3 min.
[0021] Preferably, the cathode catalyst layer formed in step S4 has a loading capacity of 0.3 to 0.6 mg / cm 2 .
[0022] Preferably, the Pt / C catalyst is composed of two substances, Pt and C, wherein in the Pt / C catalyst, the mass percentage of Pt is 40wt% to 60wt%.
[0023] The present invention also provides a low-load IrO2 water electrolysis membrane electrode, wherein the membrane electrode is prepared by adopting the above-mentioned preparation method of the low-load IrO2 water electrolysis membrane electrode.
[0024] The present invention also provides an application of a low-load IrO2 water electrolysis membrane electrode, wherein the membrane electrode is applied to a proton exchange membrane water electrolysis catalytic reaction, wherein the membrane electrode is prepared by adopting the above-mentioned preparation method of the low-load IrO2 water electrolysis membrane electrode.
[0025] As described above, the low-load IrO2 water electrolysis membrane electrode, preparation method and application thereof of the present invention have the following beneficial effects:
[0026] The present invention adopts electrostatic spinning technology to obtain a uniform fibrous IrO2 nanofiber layer, and the noble metal catalyst is located on the fiber surface and is not easy to agglomerate, thereby reducing the noble metal catalyst loading and improving the utilization rate of the catalyst; moreover, the present invention adopts Nafion as the fiber skeleton of the anode catalyst layer to obtain a uniform and continuous IrO2 nanofiber layer with a three-dimensional nanofiber network structure, which is hot-pressed and transferred onto the Nafion membrane to form an anode catalyst layer, and then the cathode catalyst layer is sprayed on the other side of the Nafion membrane, thereby efficiently and directly constructing a low-load IrO2 electrolytic water membrane electrode with a high degree of order, uniform and controllable fiber diameter and uniform distribution of catalyst particles; and the membrane electrode is a nanofiber three-dimensional network structure, which expands the three-phase interface of the membrane electrode, enhances material transfer during the water electrolysis process, and the formed continuous proton transfer channel can effectively improve proton conduction and reduce mass transfer loss. The prepared low-load IrO2 electrolytic water membrane electrode has high activity in the proton exchange membrane water electrolysis catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Shown is a SEM image of the IrO2 nanofiber layer prepared in Example 1 of the present invention.
[0028] Figure 2 Shown is a TEM image of a single fiber in the IrO2 nanofiber layer prepared in Example 1 of the present invention.
[0029] Figure 3 Shown are a high-angle annular dark field transmission electron microscope image (HAADF-TEM) and an energy dispersive spectroscopy mapping (EDS mapping) of a single fiber in the IrO2 nanofiber layer prepared in Example 1 of the present invention.
[0030] Figure 4 Shown are polarization curves of the membrane electrodes prepared in Example 1, Example 2 and Comparative Example 3 of the present invention.
[0031] Figure 5 Shown is a stability test curve chart of the membrane electrodes prepared in Example 1, Example 2 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0032] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0033] The present invention provides a method for preparing a low-load IrO2 water electrolysis membrane electrode, the preparation method comprising the following steps:
[0034] S1. Dispersing iridium dioxide and a polymer in a mixed solution to obtain a uniform spinning precursor solution; wherein the mixed solution includes a Nafion solution, water and isopropanol; the dispersion method is to disperse by ultrasonic and / or magnetic stirring, preferably, the dispersion is ultrasonic dispersion for 1 to 3 hours, and / or magnetic stirring dispersion for 1 to 3 hours;
[0035] S2, electrospinning the spinning precursor solution to obtain an IrO2 nanofiber layer on a receiving device;
[0036] S3, hot-pressing and transferring the IrO2 nanofiber layer onto the Nafion membrane to form an anode catalyst layer on the Nafion membrane;
[0037] S4. Spray the cathode catalyst slurry onto the side of the Nafion membrane away from the anode catalyst layer, and form a cathode catalyst layer on the other side of the Nafion membrane through hot pressing, thereby finally preparing a low-load IrO2 water electrolysis membrane electrode.
[0038] Specifically, in step S2, aluminum foil or silicone oil paper is adhered to the receiving device to control the spinning time. After the spinning is completed, the aluminum foil or silicone oil paper on the receiving device is peeled off and then cut into a size consistent with the size of the Nafion membrane in step S3. The actual loading capacity of the IrO2 nanofiber layer is obtained by weighing the mass of the aluminum foil or silicone oil paper before and after spinning.
[0039] In a specific embodiment of the present invention, an electrospinning technique is used to obtain a uniform fibrous IrO2 nanofiber layer, and the noble metal catalyst IrO2 is located on the fiber surface and is not easy to agglomerate, thereby reducing the noble metal catalyst loading while improving the utilization rate of the catalyst; and, Nafion is used as the fiber skeleton of the anode catalyst layer to obtain a uniform, continuous nanofiber three-dimensional network structure of IrO2 nanofiber layer, which is hot-pressed and transferred to the Nafion membrane to form an anode catalyst layer, and then the cathode catalyst layer is sprayed on the other side of the Nafion membrane, thereby efficiently and directly constructing a low-load IrO2 electrolysis water membrane electrode with a high degree of order, uniform and controllable fiber diameter, and uniform distribution of catalyst particles. As an example, the polymer in step S1 includes one of polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), and polyvinyl pyrrolidone (PVP), and the viscosity-average molecular weight of the polymer is 100,000 to 1,000,000.
[0040] Specifically, the viscosity average molecular weight of the polymer may include values within any range such as 100,000, 300,000, 600,000, 1,000,000, etc., and may be adjusted based on actual conditions.
[0041] As an example, in step S1, the mass ratio of iridium dioxide, polymer and Nafion solution is (20-100): (2-20): (50-500), and the mass concentration of the polymer in the obtained spinning precursor solution is 2wt%-10wt%.
[0042] Specifically, the mass ratio of iridium dioxide, polymer and Nafion solution may include values within any range of 20:2:50, 20:20:50, 20:2:500, 20:20:500, 100:2:50, 100:2:500, 100:20:50, 100:20:50, 100:20:50, etc.; the mass concentration of the polymer in the obtained spinning precursor solution may include values within any range of 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, etc., and may be adjusted according to actual conditions.
[0043] As an example, in step S1 , the total mass of water and isopropanol is 0 to 30 times the mass of iridium dioxide, and the mass ratio between water and isopropanol is 1:1.
[0044] Specifically, the total mass of water and isopropanol is 0 times, 5 times, 10 times, 15 times, 20 times, 25 times, 30 times, etc., of the mass of iridium dioxide. The amount of water and isopropanol added depends on the viscosity of the spinning precursor solution. It is necessary to ensure that the mass concentration of the polymer in the spinning precursor solution is 2wt% to 10wt%. If the mass concentration of the polymer in the spinning precursor solution is moderate, there is no need to add water and isopropanol. If the mass concentration of the polymer in the spinning precursor solution is no longer in the range of 2wt% to 10wt%, water and isopropanol need to be added.
[0045] As an example, the Nafion solution in step S1 is a Nafion solution with a mass percentage of 5 wt % or 20 wt %.
[0046] Specifically, the preparation method of Nafion solution is usually to add Nafion polymer into water and then dissolve it by stirring and heating; in a specific embodiment of the present invention, the Nafion polymer is a perfluorosulfonic acid-polytetrafluoroethylene copolymer.
[0047] As an example, the process parameters of electrospinning in step S2 are: positive voltage is 4 to 20 kV, negative voltage is 0 to -3 kV, ambient temperature is 15 to 25°C, relative humidity is 35% to 45%, solution advancement speed is 0.01 to 0.3 ml / h, and the distance between the syringe needle and the receiving device is 10 to 20 cm.
[0048] Specifically, electrospinning uses an electrospinning machine, and the spinning precursor is pre-injected into a syringe, and then the syringe is placed on the syringe pump of the electrospinning machine, and the distance between the syringe needle and the receiving device is set, and then other parameters are set, the spinning time is controlled, and electrospinning is performed. In a specific embodiment of the present invention, the electrospinning process is carried out using a process well known to those skilled in the art, but the process parameters need to be specifically limited. The positive voltage may include values within any range of 4kV, 8kV, 12kV, 16kV, 20kV, etc., and the negative voltage may include -0.1kV, -0.5kV, -1kV, -2kV, -3kV The ambient temperature may include values in any range of 15°C, 18°C, 20°C, 22°C, 25°C, etc. The relative humidity may include values in any range of 35%, 37%, 39%, 40%, 42%, 45%, etc. The solution advancement speed may include values in any range of 0.01ml / h, 0.05ml / h, 0.1ml / h, 0.2ml / h, 0.3ml / h, etc. The distance between the syringe needle and the receiving device may include values in any range of 10cm, 12cm, 14cm, 16cm, 18cm, 20cm, etc., and can be adjusted according to actual conditions.
[0049] In addition, the electrospinning machine will generate a high-voltage electric field when in operation. Safety education and training must be conducted before electrospinning is carried out, and the experimental progress must be closely monitored during use to ensure personal and instrument safety.
[0050] As an example, the receiving device in step S2 is a flat plate, grid or roller-shaped receiving device, and aluminum foil or silicone oil paper is adhered to the receiving device.
[0051] Specifically, the receiving device is used to receive the IrO2 nanofibers formed by electrospinning, and a flat plate receiving device or a grid receiving device is usually used. When preparing a membrane electrode with a larger area, the drum receiving device can be rotated. Aluminum foil or silicone oil paper is adhered to the receiving device so that the obtained IrO2 nanofiber layer can be peeled off from the receiving device, and then the mass of the aluminum foil or silicone oil paper before and after spinning is weighed to obtain the actual loading capacity of the IrO2 nanofiber layer.
[0052] In a specific embodiment of the present invention, the loading of the anode catalyst layer on the low-loading IrO2 water electrolysis membrane electrode finally prepared is 0.1-2 mg / cm 2 (For example, 0.1 mg / cm 2 , 0.3mg / cm 2 , 0.5mg / cm 2 , 1mg / cm 2 , 1.5mg / cm 2 , 1.7mg / cm 2 , 2mg / cm2 any range of values).
[0053] As an example, the Nafion membrane in step S3 needs to be pretreated before transfer. Specifically, the Nafion membrane is cut into the required size, placed in a 3wt% to 10wt% (such as 3wt%, 5wt%, 7wt%, 9wt%, 10wt% or any other value in the range) hydrogen peroxide solution and heated for 1 hour, then washed with ultrapure water, and then placed in a 0.5mol / L sulfuric acid solution and heated for 1 hour. After washing with ultrapure water, a pure Nafion membrane is obtained.
[0054] As an example, in step S3 , the temperature of the hot-pressing transfer is 130-140° C., the pressure of the hot-pressing transfer is 1-3 MPa, and the time of the hot-pressing transfer is 2-5 min.
[0055] Specifically, in step S3, the hot pressing transfer is carried out on a hydraulic press, and the IrO2 nanofiber layer with aluminum foil or silicone oil paper is cut into a size consistent with the size of the Nafion membrane, and then placed together on the hydraulic press; the temperature of the hot pressing transfer may include a value within any range such as 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, etc., which can be adjusted according to actual conditions; the pressure of the hot pressing transfer may include a value within any range such as 1Mpa, 1.5Mpa, 2Mpa, 2.5Mpa, 3Mpa, etc., which can be adjusted according to actual conditions; the time of the hot pressing transfer may include a value within any range such as 2min, 3min, 4min, 5min, etc., which can be adjusted according to actual conditions.
[0056] As an example, in step S4, according to the components of the cathode catalyst slurry, the cathode catalyst slurry includes 1 part of Pt / C catalyst, 1 to 10 parts (such as 1 part, 3 parts, 5 parts, 7 parts, 9 parts, 10 parts, etc.) of 5wt% Nafion solution, 5 to 15 parts (such as 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, etc.) of water and 5 to 15 parts (such as 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, etc.) of isopropanol.
[0057] Specifically, the cathode catalyst slurry is prepared by ultrasonically dispersing a certain ratio of Pt / C catalyst, 5 wt% Nafion solution, water and isopropanol.
[0058] As an example, in step S4, the temperature of hot pressing is 130-140° C., the pressure of hot pressing is 4-6 MPa, and the time of hot pressing is 1-3 min.
[0059] Specifically, the hot pressing in step S4 is also carried out on a hydraulic press, and the temperature of the hot pressing may include a value within any range such as 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, etc., which can be adjusted according to actual conditions; the pressure of the hot pressing may include a value within any range such as 4Mpa, 4.5Mpa, 5Mpa, 5.5Mpa, 6Mpa, etc., which can be adjusted according to actual conditions; the time of the hot pressing may include a value within any range such as 1min, 1.5min, 2min, 2.5min, 3min, etc., which can be adjusted according to actual conditions.
[0060] As an example, the cathode catalyst layer formed in step S4 has a loading capacity of 0.3 to 0.6 mg / cm 2 .
[0061] Specifically, the loading of the cathode catalyst layer formed on the Nafion membrane may include 0.3 mg / cm 2 , 0.4mg / cm 2 , 0.5mg / cm 2 , 0.6mg / cm 2 The value can be within any range and can be adjusted according to actual conditions.
[0062] As an example, a Pt / C catalyst is composed of two substances, Pt and C, wherein the mass percentage of Pt in the Pt / C catalyst is 40wt% to 60wt% (for example, any value within a range of 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, etc.).
[0063] The present invention also provides a low-load IrO2 water electrolysis membrane electrode, which is prepared by adopting the preparation method of the low-load IrO2 water electrolysis membrane electrode.
[0064] In addition, the present invention also provides an application of a low-load IrO2 water electrolysis membrane electrode, which is applied to a proton exchange membrane water electrolysis catalytic reaction.
[0065] In order to better understand the low-loading IrO2 water electrolysis membrane electrode, preparation method and application thereof in the present invention, the low-loading IrO2 water electrolysis membrane electrode, preparation method and application thereof in the present invention are described below with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present invention in any way.
[0066] Example 1
[0067] This embodiment provides a method for preparing a membrane electrode for water electrolysis with low IrO2 loading, and the preparation method comprises the following steps:
[0068] S1. Add 80 mg of iridium dioxide and 14 mg of PEO into a sample bottle, then add 185 mg of ultrapure water, 99 mg of 5 wt% Nafion solution and 185 mg of isopropanol in sequence, and stir magnetically for 2 h to make IrO2 evenly dispersed to obtain a uniform spinning precursor solution; wherein the viscosity-average molecular weight of PEO is 600,000;
[0069] S2. Inject the spinning precursor solution into a 1 mL syringe, and then place the syringe on the syringe pump of the electrospinning machine so that the distance between the syringe needle and the flat receiving device is 15 cm. The external positive voltage is 15 kV, the negative voltage is -2 kV, the ambient temperature is 20 ° C, and the relative humidity is 40%. Under the conditions, electrospinning is carried out at a solution propulsion speed of 0.15 ml / h. After 10 minutes, an IrO2 nanofiber layer is obtained on the flat receiving device; wherein, aluminum foil is adhered to the flat receiving device, and the IrO2 nanofiber membrane is attached to the aluminum foil. The aluminum foil adhered to the flat receiving device is peeled off and cut into a shape of 2 cm × 2 cm. By weighing the mass of the aluminum foil before electrospinning, the actual loading of the IrO2 nanofiber layer is calculated to be 0.1 mg / cm 2 ;
[0070] S3, placing the IrO2 nanofiber layer attached to the aluminum foil and a 2cm×2cm Nafion membrane on a hydraulic press, setting the temperature of hot pressing transfer to 135°C and the pressure of hot pressing transfer to 2 MPa, performing hot pressing transfer for 3 minutes, hot pressing transfer the IrO2 nanofiber layer to the Nafion membrane, and forming an anode catalyst layer on the Nafion membrane; wherein the Nafion membrane used is Nafion115 membrane;
[0071] S4. Spray the cathode catalyst slurry onto the side of the Nafion membrane away from the anode catalyst layer with a spray brush, and perform hot pressing on a hydraulic press. The hot pressing temperature is 135°C, the pressure is 6 MPa, and the hot pressing time is 2 min. A cathode catalyst layer is formed on the other side of the Nafion membrane, and finally a low-loading IrO2 water electrolysis membrane electrode is prepared, wherein the cathode catalyst slurry is prepared from 15 mg 60% Pt / C catalyst, 75 mg 5% Nafion solution, 225 mg water and 225 mg isopropanol.
[0072] The low-load IrO2 water electrolysis membrane electrode prepared in this example includes a Nafion membrane, an anode catalyst layer and a cathode catalyst layer. The actual loading of the anode catalyst layer is 0.1 mg / cm 2 In this embodiment, the prepared low-loading IrO2 water electrolysis membrane electrode is referred to as ES-0.1.
[0073] See also Figure 1 , Figure 2 , Figure 1 is a SEM image of the IrO2 nanofiber layer prepared in this example, Figure 2 This is the TEM image of a single fiber in the IrO2 nanofiber layer. It can be seen from the figure that a uniform network skeleton is formed in the IrO2 nanofiber layer prepared in this embodiment, and the fibers are complete and uniform without agglomeration. Using it in the electrolytic water catalytic reaction can effectively promote the material transfer of oxygen and water; in addition, IrO2 is evenly distributed on the fiber surface, which increases the reaction active sites, and can reduce the precious metal catalyst loading while improving the utilization rate of the catalyst.
[0074] See also Figure 3 The transmission electron microscope high-angle annular dark field image (HAADF-TEM) and energy dispersion spectrum mapping (EDS mapping) of a single fiber in the IrO2 nanofiber layer prepared in this embodiment. From left to right and from top to bottom, the first figure is a scanning transmission electron microscope high-angle annular dark field image, the second figure is a combined image of O, F, S, and Ir elements, and the rest are elemental analysis images of O, F, S, and Ir, respectively. It can be seen from the figure that the IrO2 catalyst particles are distributed on the fiber surface, and the distribution is uniform without aggregation. At the same time, the Nafion resin is evenly distributed to form a continuous proton transmission channel.
[0075] Comparative Example 1
[0076] This comparative example provides a conventional method for preparing a membrane electrode, and the preparation method comprises the following steps:
[0077] A1. Add 5 mg of iridium dioxide into a sample bottle, then add 75 mg of ultrapure water, 25 mg of 5 wt% Nafion solution and 75 mg of isopropanol in sequence, and disperse by ultrasonic for 2 h to make IrO2 evenly dispersed to obtain a uniform anode catalyst slurry;
[0078] A2, spraying the anode catalyst slurry onto the Nafion membrane with an airbrush, and hot pressing (hot pressing temperature of 135° C., hot pressing pressure of 6 MPa, hot pressing for 2 min) to form an anode catalyst layer on the Nafion membrane;
[0079] A3. Spray the cathode catalyst slurry onto the side of the Nafion membrane away from the anode catalyst layer with a spray pen, and perform hot pressing on a hydraulic press. The hot pressing temperature is 135° C., the pressure is 6 MPa, and the hot pressing time is 2 min. A cathode catalyst layer is formed on the other side of the Nafion membrane, and finally a traditional membrane electrode is prepared, wherein the cathode catalyst slurry is prepared from 15 mg of 60% Pt / C catalyst, 75 mg of 5% Nafion solution, 225 mg of water and 225 mg of isopropanol.
[0080] The actual loading of the anode catalyst layer on the membrane electrode prepared in this comparative example is 0.1 mg / cm 2 In this comparative example, the prepared membrane electrode is referred to as: CCM-0.1.
[0081] Example 2
[0082] This reference example provides a method for preparing a low-load IrO2 water electrolysis membrane electrode. The difference between the preparation method and that in reference example 1 is that in step A1, 20 mg of iridium dioxide is added to a sample bottle, followed by adding 300 mg of ultrapure water, 100 mg of 5 wt% Nafion solution and 300 mg of isopropanol in sequence, and ultrasonically dispersed for 2 hours to uniformly disperse the IrO2 to obtain a uniform anode catalyst slurry; the other steps and methods are the same as those in reference example 1 and will not be repeated here.
[0083] The actual loading of the anode catalyst layer on the membrane electrode prepared in this comparative example is 0.1 mg / cm 2 In this comparative example, the prepared membrane electrode is referred to as: CCM-1.
[0084] Application Example 1
[0085] This application example provides an application of a membrane electrode, and the membrane electrodes (ES-0.1, CCM-0.1, CCM-1) prepared in Example 1, Comparative Example 1 and Comparative Example 2 are applied to a proton exchange membrane water electrolysis catalytic reaction.
[0086] Polarization curve test:
[0087] Each membrane electrode (ES-0.1, CCM-0.1, CCM-1) was placed in a small water electrolysis fixture, and 80°C deionized pure water was passed into the anode. The whole system was placed in an environment of 80°C, and the current density of the water electrolysis was set to 0-2A / cm 2 Tests were carried out to obtain the polarization curves of each membrane electrode for water electrolysis, see Figure 4 As shown by Figure 4 It can be seen that the performance of ES-0.1 is equivalent to that of traditional CCM-1 and slightly better when the loading of IrO2 catalyst in ES-0.1 is reduced by ten times; while the performance of CCM-0.1 with the same catalyst loading is very poor, which shows that the membrane electrode prepared in the present invention can effectively improve the utilization rate of water electrolysis catalyst and improve the reaction performance.
[0088] Stability test:
[0089] Each membrane electrode (ES-0.1, CCM-0.1, CCM-1) was placed in a small water electrolysis fixture and tested for stability at 80°C. During the test, ultrapure water was passed into the anode and the current density was set to 1A / cm 2The stability test results are shown in Figure 5 As shown by Figure 5 It can be seen that after running for 100 hours, the performance of ES-0.1 remains very good, which is similar to the performance presented by CCM-1. However, the stability presented by CCM-0.1 deteriorates rapidly with the extension of running time. After running for about 20 hours, it stops because the protection voltage is reached.
[0090] In summary, the present invention adopts electrospinning technology to obtain a uniform fibrous IrO2 nanofiber layer, and the precious metal catalyst is located on the fiber surface and is not easy to agglomerate, thereby reducing the precious metal catalyst loading while improving the utilization rate of the catalyst; moreover, the present invention adopts Nafion as the fiber skeleton of the anode catalyst layer to obtain a uniform and continuous nanofiber three-dimensional network structure of IrO2 nanofiber layer, which is hot-pressed and transferred to the Nafion membrane to form an anode catalyst layer, and then the cathode catalyst layer is sprayed on the other side of the Nafion membrane, thereby efficiently and directly constructing a low-load IrO2 electrolytic water membrane electrode with a high degree of order, uniform and controllable fiber diameter and uniform distribution of catalyst particles; and the membrane electrode is a nanofiber three-dimensional network structure, which expands the three-phase interface of the membrane electrode, enhances material transfer during the water electrolysis process, and the continuous proton transfer channel formed can effectively improve proton conduction and reduce mass transfer loss. The prepared low-load IrO2 electrolytic water membrane electrode has high activity in the proton exchange membrane water electrolysis catalytic reaction. Therefore, the present invention effectively overcomes various shortcomings in the prior art and has high industrial utilization value.
[0091] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a low-load IrO2 water electrolysis membrane electrode, characterized in that: The preparation method comprises the following steps: S1, dispersing iridium dioxide and a polymer in a mixed solution to obtain a uniform spinning precursor solution; wherein the mixed solution comprises a Nafion solution, water and isopropanol; S2, electrospinning the spinning precursor solution to obtain an IrO2 nanofiber layer on a receiving device; S3, hot-pressing and transferring the IrO2 nanofiber layer onto a Nafion membrane to form an anode catalyst layer on the Nafion membrane; S4. Spray the cathode catalyst slurry onto the side of the Nafion membrane away from the anode catalyst layer, and form a cathode catalyst layer on the other side of the Nafion membrane through hot pressing, thereby finally preparing a low-load IrO2 water electrolysis membrane electrode.
2. The method for preparing a low-load IrO2 water electrolysis membrane electrode according to claim 1, characterized in that: Step S1 includes one or a combination of the following conditions: The polymer includes one of polyethylene oxide, polyvinyl alcohol, polyacrylonitrile and polyvinyl pyrrolidone, and the viscosity average molecular weight of the polymer is 100,000 to 1,000,000; The mass ratio of the iridium dioxide, the polymer and the Nafion solution is (20-100): (2-20): (50-500), and the mass concentration of the polymer in the obtained spinning precursor solution is 2wt%-10wt%; The total mass of the water and the isopropanol is 0 to 30 times the mass of the iridium dioxide, and the mass ratio between the water and the isopropanol is 1:1; The Nafion solution is a Nafion solution with a mass percentage of 5wt% or 20wt%.
3. The method for preparing a low-load IrO2 water electrolysis membrane electrode according to claim 1, characterized in that: The process parameters of the electrospinning in step S2 are: positive voltage of 4 to 20 kV, negative voltage of 0 to -3 kV, ambient temperature of 15 to 25 ° C, relative humidity of 35% to 45%, solution propulsion speed of 0.01 to 0.3 ml / h, and the distance between the syringe needle and the receiving device is 10 to 20 cm.
4. The method for preparing a low-load IrO2 water electrolysis membrane electrode according to claim 1, characterized in that: In step S2, the receiving device is a flat plate, grid or roller-shaped receiving device, and aluminum foil or silicone oil paper is adhered to the receiving device.
5. The method for preparing a low-load IrO2 water electrolysis membrane electrode according to claim 1, characterized in that: The Nafion membrane in step S3 needs to be pretreated before transfer. Specifically, the Nafion membrane is cut into the required size, placed in a 3wt% to 10wt% hydrogen peroxide solution and heated for 1 hour, then washed with ultrapure water, and then placed in a 0.5mol / L sulfuric acid solution and heated for 1 hour. After washing with ultrapure water, a pure Nafion membrane is obtained.
6. The method for preparing a low-load IrO2 water electrolysis membrane electrode according to claim 1, characterized in that: The temperature of the hot press transfer in step S3 is 130-140° C., the pressure of the hot press transfer is 1-3 MPa, and the time of the hot press transfer is 2-5 min.
7. The method for preparing a low-load IrO2 water electrolysis membrane electrode according to claim 1, characterized in that: Step S4 includes one or a combination of the following conditions: According to the components of the cathode catalyst slurry, the cathode catalyst slurry includes 1 part of Pt / C catalyst, 1 to 10 parts of 5 wt% Nafion solution, 5 to 15 parts of water and 5 to 15 parts of isopropanol; The temperature of the hot pressing is 130-140°C, the pressure of the hot pressing is 4-6Mpa, and the time of the hot pressing is 1-3min; The cathode catalyst layer formed on the Nafion membrane has a loading capacity of 0.3 to 0.6 mg / cm 2 .
8. The method for preparing a low-load IrO2 water electrolysis membrane electrode according to claim 6, characterized in that: The Pt / C catalyst is composed of two substances, Pt and C, wherein the mass percentage of Pt in the Pt / C catalyst is 40wt% to 60wt%.
9. A low-load IrO2 water electrolysis membrane electrode, characterized in that: The membrane electrode is prepared by the preparation method of low-load IrO2 water electrolysis membrane electrode according to any one of claims 1 to 8.
10. An application of a low-load IrO2 water electrolysis membrane electrode, characterized in that: The membrane electrode is applied to the proton exchange membrane water electrolysis catalytic reaction, wherein the membrane electrode is prepared by the preparation method of the low-load IrO2 water electrolysis membrane electrode according to any one of claims 1 to 8.
Citation Information
Patent Citations
Electrically conductive nanofibers for electrolysis of polymer-based membranes
CN114127336A
Method for preparing PEM membrane electrode for hydrogen production by electrolyzing water through electrostatic spinning method
CN114807974A
IrOX (at) ATO nanofiber, preparation method thereof and application of IrOX (at) ATO nanofiber in electrolyte membrane dehumidifier
CN116288814A